Analysis of The Pilot Fall from The Pilot Ladder While Climbing to The Board of MV Van Star in The Rouen River Area - Huda, Samsul; Fatimah, Fatimah; Zulkaranen, Iris Azhari (RSF Conference Series: Engineering and Technology, 2023)
Therefore, it is important to take care to protect both the equipment and current human resources on board, given how often it is for work accidents to happen there, particularly during the pilot transfer phase—especially causing severe pain for everyone who is exposed to it, as in workplace mishaps involving stair falls, stairway sliding, or other contributing elements like sea waves and wind speed. The goals of this study are to identify the variables that lead to pilot falls, how to maintain pilot ladders, and how to enable pilots to board ships securely. In order to ensure that the research process is in line with the facts, researchers employ theoretical underpinnings as guidelines and qualitative approaches that place a greater emphasis on technical factors. When conducting field research, information is gathered through observation, documentation studies, interviews, and literature reviews. To address the problem formulation, the gathered data was then examined utilizing a fishbone diagram analysis technique. This study shows that during the maneuvering of the MV pilot pick-up, the pilot falls from the deck side of the boat via the pilot ladder. Van Star in the Rouen River area, specifically internal factors, such as a lack of safety awareness and disregard for pilot ladder pilots, and external factors, such as the ship being engaged in the process of maneuvering a pilot pick-up, which resulted in the creation of high waves as the boat pilot approached. It demonstrates that the upkeep and use of the pilot rung, specifically, a deeper understanding of pilot ladder arrangements and performing PMS (plan maintenance system), notably on pilot ladders, are necessary if the ship's draft exceeds the prescribed limit in order to prevent the accident.